Job Satisfaction and Organizational Citizenship Behavior (OCB) in Nurses - Dulahu, Wirda Y; Mun'Im, Abdul; Hiola, Dewi Suryaningsih; Hunawa, Rachmawaty D (Indonesian Journal of Global Health Research, 2024)
The quality of service in hospitals can be improved if individuals, in this case nurses, have Organizational Citizenship Behavior (OCB). OCB is a form of behavior that is a choice of individual initiative and is not related to the organization's formal reward system but in aggregate increases organizational effectiveness. Objective: This research aims to determine the relationship between the level of job satisfaction and the OCB of nurses in Dr. RSUD. M.M Dunda Limboto inpatient ward. Method: Quantitative research method, Analytical Survey research design with a Cross-Sectional approach. The population in this study was 215 nurses and the sample used was 121 inpatient nurses, with a sampling technique using purposive sampling. This research uses the Spearman Rank Test. Results: the research results obtained a correlation coefficient of r= 0.342 (p-value = 0.000 or < 0.005), meaning that there is a relationship between job satisfaction and the level of OCB of nurses in the inpatient room at Dr. M.M Dunda Limboto. Conclusions: It is expected that hospital institutions can pay attention to the factors that influence job satisfaction in nurses so that they have a positive impact on the level of Organizational Citizenship Behavior in nurses.